Bioethical Questions of Animals in Sport - Bruno Ćurko (Pannoniana, 2020)
Animals are a part of sport industries, from the so-called traditions such as fox hunting and bullfighting, horse and dog racing, to the cruel examples of hare coursing, rodeo, and orangutan boxing (Thailand), to cock and dog f ights. These are prominent examples of animal exploitation serving our human entertainment. In my presentation, I will try to identify some of the essential questions considering animal use in sports. Some of these questions are: Can we justify animal exploitation in the name of tradition? Can we take into consideration the well-being of sport animals before, during, and after their competitive career? How much could and should the imminent risk of animal stress, injuries, and fatalities prevent us from their exploitation in sports? If animals are ready to obey demands we set upon them, should we abuse them for our entertainment and sport?